Global, regional, and national temporal trends in mortality and disease burden of nasopharyngeal carcinoma attributable to smoking from 1990 to 2021 and predictions to 2040 - Defeng Liu; Lulu Zhuang; Yueze Li; Jinming Yu; Minghuan Li (Tobacco Induced Diseases)
Introduction Smoking is a major environmental risk factor for nasopharyngeal carcinoma (NPC), but the global burden and epidemiological trends of NPC attributable to smoking remain unclear.